Beyond the masculinity of kingship: the making of a modern queen in early second millennium Sri Lanka - Shirley, Bruno M. (Modern Asian studies, 2024)
Modern historians have repeatedly cast Sri Lanka’s historical female monarchs as ‘queens’, without critically reflecting on the conceptual limits and nuances of that term. Through a close examination of sources from the early second millennium, and their reception by scholars from the colonial period onwards, I demonstrate that Sri Lanka’s female monarchs—particularly Līlāvatī of Poḷonnaruva (r. 1197-1200, 1209, and 1210)—engaged in a more creative and subversive performance of gender than modern ‘queenship’ allows. In particular, I argue, a discourse of kingship’s inherent masculinity, advanced in literary and didactic texts written primarily by male monastics, was too-willingly accepted by colonial-period scholars. Closer attention to the material evidence of Līlāvatī’s reign, however, challenges this discourse and further suggests a politics of gender beyond the binary.